VARIABILITY IN THE δ13C OF LOWER PALAEOZOIC PALYNOMORPHS: IMPLICATIONS FOR THE INTERPRETATION OF ANCIENT MARINE SEDIMENTS - Lecuyer C.; Paris F. (My University, 1997)
We have analyzed the stable carbon isotope ratios of various organic-walled microfossils preserved in marine sediments of Silurian and Devonian age. The aim of this study is to determine the amplitude of isotopic fractionations among the different extinct palynomorph groups. Twenty six samples of marine palynomorphs have δ13C values in the range -30.0%% to -26.3%% whereas two samples, likely of terrestrial origin (tracheids and woody tissue), have the highest δ13C values (-24.8%% and -23.3%%). Among six sediments that only contain marine palynomorphs, three show δ13C variations of 0.8, 1.0 and 2.5%%, respectively, whereas the others do not show significant difference. In the presence of fragments of woody tissue mixed with the marine plankton, these internal isotopic variations may reach about 4%%. The bulk δ13C values of organic matter in these ancient marine sediments are interpreted as average values which integrate, in addition to chemical characteristics of surface waters (e.g. [CO2]aq), source- and species-dependent isotopic compositions. The possible occurrence of such δ13C heterogeneities at the scale of a sediment sample could result at least from three kinds of material fluxes: (1) autotroph and heterotroph elements from the water column; (2) oceanic current and river inputs; and (3) selective molecular preservation related to specific biochemical structures.
Keywords: CARBON ISOTOPE; MARINE SEDIMENT; ORGANIC MATTER; PALAEOZOIC; Paleozoic; Палеозой